Heat shock proteins as biomarkers of lung cancer. Issue 6 (2nd June 2020) - Mittal, Sonam; Rajala, Maitreyi S.
ABSTRACT: Heat shock proteins are known to be associated with a wide variety of human cancers including lung cancer. Overexpression of these molecular chaperones is linked with tumor survival, metastasis and anticancer drug resistance. In recent years, heat shock proteins are gaining much importance in the field of cancer research owing to their potential to be key determinants of cell survival and apoptosis. Lung cancer is one of the most common cancers diagnosed worldwide and the association of heat shock proteins in lung cancer diagnosis, prognosis and as drug targets remains unresolved. The aim of this review is to draw the importance of heat shock protein members; Hsp27, Hsp70, Hsp90, Hsp60 and their diagnostic and prognostic implications in lung cancer. Based on the available literature heat shock proteins can serve as biomarkers and anticancer drug targets in the management of lung cancer patients.